Bulk scale synthesis of high-performance carbon nanomaterial from biogas plant residual waste: Tuned porosity and composition for advanced supercapacitor applications - Pathak, Mayank; Moravkova, Zuzana; Tatrari, Gaurav; Bhatt, Diksha; Wadhwa, Priyanka; Dhali, Sunil; Sahoo, Nanda Gopal (Elsevier BV, 2024)
Carbon based nanomaterials with tuned porosity and compositions are of great interest in terms of energy storing materials. Nevertheless, it is still a challenge to produce such nanostructures on a large scale in cost-effective manner. In this work, we demonstrate that carbon nanomaterial (CNM) can be prepared using biogas plant residual waste (BPRW) as the precursor on a bulk scale under the specific two step pyrolysis technique. The optimized process along with the catalyst used is crucial as the simple pyrolysis of precursor can only produce traditional activated carbon with significantly lower specific capacitance values. The spherical structure of silica nanoclusters and graphitic skeleton of synthesized CNM confirmed with the help of FE-SEM, AFM and HR-TEM along with Raman and XRD while EDX, XPS, and FT-IR studies confirm the presence of various functional groups along with their respective percentage composition. These CNMs show mesoporous structure of the nanomaterial. Among three different aqueous electrolytes, the maximum specific capacitance of 371.88 Fg(-1) at 0.5 Ag-1 current density in 1 M H2SO4 indicates its suitability for the practical supercapacitor applications. The fabricated symmetric supercapacitor device using CNMs as the electrode material and 1 M H2SO4 as the electrolyte shows very good specific capacitance value with the high energy density of 34.4 Whkg(-1) corresponding to 360 Wkg(-1) power density along with the good cyclic stability over 10,000 cycles of charge-discharge. This innovative technique paves the way towards upcycling any lignin containing waste material into carbon-based nanomaterial on a bulk scale by an effective method, which can be further used as high-performance electrode material for energy storage applications like in supercapacitors and batteries.